1995
DOI: 10.1002/aja.1002040305
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fibronectin expression during gastrulation and heart formation in the rat embryo

Abstract: By utilizing myosin immunostaining, we were able to identify early rat myocardium as a thin epithelial sheet and realized that its cohesive movement toward the midline leads to the straight heart tube formation. Localization study of fibronectin mRNA and protein was, therefore, carried out to investigate its tissue origin and possible roles in facilitating mesoderm migration and heart formation. Fibronectin mRNAs were first detected throughout the mesoderm during the early primitive streak stage, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…FN functions in cell-cell and cell-ECM interactions, embryonic differentiation, wound healing, and neoplastic transformation (McDonagh, 1981;Dufour et al, 1988). In the rat embryo, FN mRNA expression is elevated in the endocardium of the early heart tube, and FN protein later becomes uniformly distributed in the ECM (cardiac jelly) between the myocardium and endocardium of the heart tube (Suzuki et al, 1995). FN is important in the migration of precardiac cells and the development of cardiac cushion cells (Linask and Lash, 1986;Icardo et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…FN functions in cell-cell and cell-ECM interactions, embryonic differentiation, wound healing, and neoplastic transformation (McDonagh, 1981;Dufour et al, 1988). In the rat embryo, FN mRNA expression is elevated in the endocardium of the early heart tube, and FN protein later becomes uniformly distributed in the ECM (cardiac jelly) between the myocardium and endocardium of the heart tube (Suzuki et al, 1995). FN is important in the migration of precardiac cells and the development of cardiac cushion cells (Linask and Lash, 1986;Icardo et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…DeHaan (1963) concluded that the active process resulting in lateral to ventral folding at the level of the AIP likely occurs as a result of the mobility of clusters of precardiac cells. However, more recent evidence suggests that the underlying endoderm may also participate in this process (Suzuki et al 1995). Thus, it is likely that the process of lateral to ventral folding occurs as a result of an interplay between the overlying splanchnic mesoderm and the underlying endoderm, possibly because of differential growth between these two layers and the embryo proper.…”
Section: Gata5 Gata6mentioning
confidence: 99%
“…During heart development, Fn substrates are required to support the migration of precardiac mesoderm during gastrulation 31,32 and mesenchymal cells during cushion formation. 33 Curiously, in situ hybridization ( Figure 5) has suggested that cardiac jelly Fn is strongly expressed by endocardial cells with virtually no contribution from the myocardium; because Fn is expressed by early myocardial cells in chick embryos, 20 hybridization at earlier stages in mouse development will clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…28 It is of interest that Fn expression in adult myocytes and cardiac fibroblasts is strongly regulated by cytokines. 29,30 Hence, we are investigating the Fn phenotype in RBP-null embryos using a microarray approach to identify (1) matrix components that may be misregulated and (2) possible roles for extracellular proteases and protease inhibitors.During heart development, Fn substrates are required to support the migration of precardiac mesoderm during gastrulation 31,32 and mesenchymal cells during cushion formation. 33 Curiously, in situ hybridization ( Figure 5) has suggested that cardiac jelly Fn is strongly expressed by endocardial cells with virtually no contribution from the myocardium; because Fn is expressed by early myocardial cells in chick embryos, 20 hybridization at earlier stages in mouse development will clarify this issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation